2013
DOI: 10.1523/jneurosci.3206-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Aging-InducedNrf2-AREPathway Disruption in the Subventricular Zone Drives Neurogenic Impairment in Parkinsonian Mice viaPI3K-Wnt/β-CateninDysregulation

Abstract: Aging and exposure to environmental toxins including MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) are strong risk factors for developing Parkinson's disease (PD), a common neurologic disorder characterized by selective degeneration of midbrain dopaminergic (DAergic) neurons and astrogliosis. Aging and PD impair the subventricular zone (SVZ), one of the most important brain regions for adult neurogenesis. Because inflammation and oxidative stress are the hallmarks of aging and PD, we investigated the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
196
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(197 citation statements)
references
References 119 publications
1
196
0
Order By: Relevance
“…Aged SVZ NSPCs form smaller neurospheres and adherent colonies compared with young adult NSPCs, and this correlates with their decreased proliferation capacity in vitro (Ahlenius et al., 2009; Corenblum et al., 2016; Daynac et al., 2014, 2016; L'Episcopo et al., 2013; Zhu et al., 2014). We also observed a proliferation defect in NSPCs derived from the aged mice (Figures S1B,C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aged SVZ NSPCs form smaller neurospheres and adherent colonies compared with young adult NSPCs, and this correlates with their decreased proliferation capacity in vitro (Ahlenius et al., 2009; Corenblum et al., 2016; Daynac et al., 2014, 2016; L'Episcopo et al., 2013; Zhu et al., 2014). We also observed a proliferation defect in NSPCs derived from the aged mice (Figures S1B,C).…”
Section: Resultsmentioning
confidence: 99%
“…Aging is associated with reduced neurogenesis in the mouse SVZ and SGZ (Encinas et al., 2011; Enwere et al., 2004; Lugert et al., 2010; Luo, Daniels, Lennington, Notti & Conover, 2006), which might lead to decreased olfactory function and cognitive hippocampus‐dependent impairment (Goncalves et al., 2016; Lledo & Valley, 2016). This age‐associated neurogenic decline appears to be caused both by a depletion in the NSPC pool of the aged niche (Ahlenius, Visan, Kokaia, Lindvall & Kokaia, 2009; Bouab, Paliouras, Aumont, Forest‐Berard & Fernandes, 2011; Corenblum et al., 2016; Enwere et al., 2004; Luo et al., 2006; Maslov, Barone, Plunkett & Pruitt, 2004; Molofsky et al., 2006; Stoll et al., 2011) and by the decreased capacity of the remaining NSPCs to sustain proliferation and neuronal differentiation, as revealed by in vitro studies (Ahlenius et al., 2009; Apostolopoulou et al., 2017; Corenblum et al., 2016; Daynac, Morizur, Chicheportiche, Mouthon & Boussin, 2016; Daynac et al., 2014; L'Episcopo et al., 2013; Shi et al., 2017; Zhu et al., 2014). NSPCs undergo cell autonomous age‐related changes that affect intracellular molecular pathways, including the altered expression of telomerase and cell cycle regulators, which have been linked to the decline in NSPC proliferation upon aging (Caporaso, Lim, Alvarez‐Buylla & Chao, 2003; Molofsky et al., 2006; Nishino, Kim, Chada & Morrison, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Wnt signaling inhibits GSK-3β activity [37]. To evaluate the role of the Wnt/β-catenin signaling pathway in NaIO 3 -treated L2.3 cells, we performed real-time PCR assays to evaluate the expression levels of Axin2, β-catenin and Gsk-3β.…”
Section: Resultsmentioning
confidence: 99%
“…The Wnt/β-catenin signal transduction pathway plays an important role in the proliferation capacity of L2.3 cells. L'Episcopo et al found that oxidative injury to RGCs leads to downregulation of the expression of β-catenin and the overexpression of GSK-3β, whereas inhibiting Wnt/β-catenin signaling using small interfering RNA to inhibit GSK-3β expression or antagonize GSK-3β activity reverses neurogenic impairment [37,43]. These findings indicate that the Wnt/β-catenin/GSK-3β pathway acts to regulate the proliferation of injured RGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding middle-aged mice with already impaired NS/PC proliferation and generation of DCX + young neurons with an NO-donating fl urbiprofen derivative, which amongst others has antioxidative properties, restores these NS/PC functions almost to levels of young controls [ 69 ], suggesting causal involvement of oxidative stress in age-related decline of NS/ PC functions. These are related to altered wnt-signaling [ 69 ] and a crosstalk between Sirt-1-and wnt-signaling was reported in a different context earlier [ 70 ]. Whether this aging-related, oxidation state-dependent, wnt-mediated decline in NS/PC functions is determined by NAD + -dependent Sirt-1 activation needs further clarifi cation.…”
Section: Responses On the Organ Level That May Be An Adverse Outcome mentioning
confidence: 95%